“IT’S QUICKLY OVER AND EASILY ACCESSIBLE”: SOCIOLOGICAL INSIGHTS INTO NON-INVASIVE AESTHETIC SURGERY AMONG WOMEN IN CROATIA - BRSTILO LOVRIĆ, Ivana; PLENKOVIĆ, Mateja (Studia Universitatis Babeș-Bolyai Sociologia, 2025)
Aesthetic surgery is a global phenomenon, with millions of users worldwide. This study explores the sociological dimensions of non-invasive aesthetic procedures, based on semi-structured interviews with 18 women in Croatia who have undergone such treatments, primarily dermal fillers and Botox, most commonly applied to the face area. The analysis identified a range of motivations, including dissatisfaction with body image, the desire to reduce visible signs of ageing, enhance appearance, and improve quality of life. For some, exposure to social media, particularly Instagram, and global celebrity culture served as inspiration. However, most participants framed their decisions in terms of personal aspirations for self-enhancement rather than conformity to dominant beauty ideals. Body image prior to the procedures ranged from negative to positive. Most participants reported increased satisfaction following treatment, and many noted that their appearance became a frequent subject of social commentary, revealing the potential for stigma directed at those who engage in aesthetic modification. Nearly all expressed interest in further procedures, whether to maintain current results or pursue new goals. These findings suggest that aesthetic surgery is a complex phenomenon in which the body becomes a site of transformation and potential, shaped by late modernity’s emphasis on self-actualisation and the body as an ongoing identity project.